Lego DC super hero girls. Brain drain [videorecording (DVD)] - Adams, Jeremy (Screenwriter); Fairweather, Anais; DeLisle, Grey; Selich, Ashlyn; Dunn, Teala (DC SuperHero girls. Videos., 2017)
When Supergirl, Wonder Woman, and Batgirl can't remember their Monday at Super Hero High, they must retrace their steps to uncover who stole their memories and why!